CNP Signal Peptide in Patients with Cardiovascular Disease - Lee, Jacqui; Than, Martin; Aldous, Sally; Troughton, Richard; Richards, Mark; Pemberton, Chris J. (Frontiers in Cardiovascular Medicine, 2015)
We have previously reported that signal peptide fragments of C-type natriuretic peptide (CNP) are present in the human circulation. Here, we provide the first preliminary assessment of the potential utility of CNP signal peptide (CNPsp) measurement in acute cardiovascular disease. Utilising our specific and sensitive immunoassay, we assessed the potential of CNPsp measurement to assist in the identification of acute coronary syndromes in 494 patients presenting consecutively with chest pain. The diagnostic and prognostic potential of CNPsp was assessed in conjunction with a contemporary clinical troponin I assay, an investigational highly sensitive troponin T assay and NT-proBNP measurement. Utility was assessed via receiver operator curve characteristic analysis. CNPsp did not identify patients with myocardial infarction (MI) or those with unstable angina, nor did it assist the diagnostic ability of clinical or investigational troponin measurement. CNPsp levels were significantly elevated in patients presenting with atrial fibrillation (P<0.05) and were significantly lower in those with a history of previous MI (P<0.05). CNPsp could identify those at risk of mortality within 1 year (P<0.05) and also could identify those at risk of death or re-infarction within 1 year (P<0.01). This is the first exploratory report describing the potential of CNPsp measurement in acute cardiovascular disease. Whilst CNPsp does not have utility in acute diagnosis, it may have potential in assisting risk prognosis with respect to mortality and re-infarction.